2005
DOI: 10.1016/j.jasms.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of zinc finger cysteines: Chemical modifications within labile zinc fingers in estrogen receptor

Abstract: Estrogen receptor (ER, alpha isoform) is a 67 kDa zinc finger transcription factor that plays a fundamental role in both normal reproductive gland development and breast carcinogenesis, and also represents a critical molecular target for breast cancer therapy. We are investigating the structural consequences of chemical exposures thought to modify essential zinc finger cysteine residues in human ER. The current study employs mass spectrometry to probe ER zinc finger structural changes induced by a redox-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Cys 530 was observed only in Glu-C digests, and Cys 381 was not observed at all. Our studies on the oxidation of cysteine residues in the DBD have been described elsewhere (8,10,11).…”
Section: Monitoring Of Cysteine Residuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cys 530 was observed only in Glu-C digests, and Cys 381 was not observed at all. Our studies on the oxidation of cysteine residues in the DBD have been described elsewhere (8,10,11).…”
Section: Monitoring Of Cysteine Residuesmentioning
confidence: 99%
“…The LC-MS/MS spectrum of the MH 2 2ϩ is illustrated in Fig. 4A: b 1 and b 2 ions confirm N-terminal acetylation, whereas y 2 and y 3 exclude the possibility of the acetyl group being located on Lys 8 . Ac-2 TMTLHTKASGMALLHQIQGNE was also identified with a Mascot score of 72 (Glu-C digest; spectrum not shown).…”
Section: Observation Of Acetylated Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…ER in living cells was also subject to oxidative damage induced by both H 2 O 2 and menadione as demonstrated by a loss of DNA binding activity and the ability of ER to activate transcription of a reporter construct. Mass spectrometry studies revealed that ZF2 is the primary target of oxidative damage via disulfide formation and subsequent loss of Zn 2+ (Figure 3, B) [105, 106]. Being more flexible than ZF1, the “open” structure of ZF2 could allow easier access of ROS to catalyze disulfide bond formation.…”
Section: Nrs Containing Redox Sensitive Thiolsmentioning
confidence: 99%
“…Some reactants (e.g., diamide) produce thiol-reversible loss of ER DNA-binding; others (e.g., iodoacetamide, bromobimane, K3) produce irreversible structural and functional changes in ER. Understanding the various types of structural changes produced in ER by either environmental or endogenous exposures to redox-active and arylating quinones is now possible using optimized immunoaffinity enrichment procedures and modern mass spectrometry (MS) techniques (Whittal et al 2000;Baldwin and Benz 2002;Meza et al 2003;Atsriku et al 2005). Figure 5 shows the functional domains of ER, highlighting the zinc finger structures and Figure 5 Thiol arylation of ER assessed by mass spectrometry.…”
Section: Quinone Effects On Hormone-dependent Pathwaysmentioning
confidence: 99%